Pymes functional areas performance in the west central metropolitan area - AMCO business and social wealth: human resource management (2020)
Human Resource practices have varied according to the concept we have of the importance of people in modern business organizations. By developing the concept of the value of information and learning companies, people return to the centrality because in them lies the ability to learn and it´s them who constitute the main strategic and competitive advantage of the organization.